Alur Tinjauan Literatur Terhadap Evaluasi Sistem Administrasi Pajak Modern: Masukan Untuk Penelitian Selanjutnya - Abdul Rahman (Jurnal Transformasi Administrasi, 2017)
The advance of technology, development of global economy, and economic crisis force countries around the world to conduct the continuous improvement of financial system including the tax system. Interestingly, one of the elements most often done is that modernizing the tax administration system because of public demands for better tax services and the government need for an increasing the tax revenue. It is not surprising, if this element takes a considerable cost portion from public money, therefore its role to tax system needs to be evaluated. By conducting a systematic literature review flow, this study provides theoretically and empirically insights in order to evaluate a modern tax administration system (MTAS).By using data simulation, I detect the type of study, five most important stakeholders, dimension, and driving factors regarding the applying MTAS. This study is expected to enrich the existing literature through a systematic literature review flow to unify former studies both theoretically and empirically, so that it can result relevant insights for the evaluation of MTAS and to propose the research agenda in the future.